Pengaruh Kompensasi, Lingkungan Kerja, Dan Keseimbangan Kehidupan Kerja Terhadap Kinerja Karyawan Quality Group PT Bumi Jatikalang Sejahtera - Robbany, Akhmad Sa`ad Ainur; Khalikussabir, Khalikussabir; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study seeks to examine the impact of compensation, work environment, and work-life balance on employee performance at Quality Group Sidoarjo, PT Bumi Jatikalang Sejahtera. The research utilized a quantitative methodology, with data collected through questionnaires distributed to 34 employees at the Quality Group Sidoarjo office of PT Bumi Jatikalang Sejahtera. Data were analyzed using multiple linear regression techniques. The findings reveal that compensation does not significantly affect employee performance, the work environment has a significant influence, while work-life balance does not show a significant effect. Keywords: Employee Performance, Compensation, Work Environment Work-Life Balance.